Search for supersymmetric particles at 130 GeV < √s <140 GeV at LEP - Dova, María Teresa (1996)
A search for supersymmetric particles (charginos, neutralinos, sleptons and stop quarks) has been performed with data collected by the L3 detector during the November 1995 run of the LEP collider at centre of mass energies between 130 and 140 GeV with a total integrated luminosity of 5.1 pb−1. We observe no signal for supersymmetric particles and we set improved exclusion limits on their production cross sections and masses.